CURRENT STATE OF AGRICULTURAL INSURANCE PRACTICE AND WAYS OF ITS DEVELOPMENT - Kuldoshev Ilyas Shukhratovich (European Science Publishing, 2024)
This article describes the current state of agricultural insurance in Uzbekistan, the ways of its application by developed and developing countries. Also, there have been made some suggestions on minimizing the damage seen in our agriculture, and helping farmers and landowners financially maintain their business by applying current achievements of foreign experience of agricultural insurance to the agriculture of Uzbekistan.
Keywords: Insurance, insurance losses, reinsurance, actuarial calculation, insurance companies, tariff rates, insurance premiums.